Analysis of a 3G network QoS in urban and rural area in Malaysia / Mohd Fadzli Hashim - Hashim, Mohd Fadzli (2013)
This work is an investigation on mobile QoS (Quality-of-Service) of a 3G network in an urban and rural area. The investigation was done by analyzing raw data acquired through drive tests carried out in the different areas. There were three main parameters of network QoS that were focused on in the analysis. They are availability, dependability and reliability. Availability is determined through analyzing RSCP values meanwhile dependability is determined through analyzing blocked call events and reliability is determined through analyzing Ec/No values and dropped call events. The results of the analysis were used to determine the impact of different terrain and population density in urban and rural areas on a 3G network QoS. Handover failures and packet data performance will also be analyzed.